Endovascular comprehensive treatment of post-traumatic superior mesenteric arteriovenous fistula: case report and literature review - Wang, Hongxin; Zheng, Kai; Nie, Qiangqiang; Yang, Bo; Fan, Xueqiang; Liu, Peng; Ye, Zhidong (Frontiers in Cardiovascular Medicine, 2024)
Background: Superior mesenteric arteriovenous fistula is a rare and difficult complication after abdominal trauma. Utilizing comprehensive endovascular treatment represents an effective approach to managing this condition.We report a case involving a 53-year-old female with a history of trauma who presented with complaints of abdominal pain, malaise, and melena. A computed tomographic scan revealed the presence of a superior mesenteric arteriovenous fistula. The fistula was occluded using four Interlock detachable coils, and a covered stent was positioned over the arteriovenous fistula in the superior mesenteric artery. Following endovascular treatment, the patient's abdominal pain and melena symptoms disappeared.Utilizing covered stents and Interlock detachable coils for endovascular treatment of a superior mesenteric arteriovenous fistula proves to be both feasible and highly effective.